Some asymptotic formulae for the sums of multiplicative function and its applications (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. С. Файнлейб. Некоторые асимптотические формулы для сумм мультипликативных функций и их приложения A. Fainleibas. Kai kurios asimptotinės formulės multiplikatyvinių funkcijų sumoms ir jų pritaikymai